The weaponisation of the Eastern Mediterranean: refugees as the Trojan horse for diplomatic bargaining - Filippidou, Anastasia (Taylor & Francis, 2022)
By focusing on the eastern Mediterranean, the chapter examines how states use forced seaborne population movement to enhance the states’ diplomatic approaches and bargaining methods. To this end, the chapter explores how people interact with nature and territory in pursuit of security and the relationship between politics, location, and material things. The chapter highlights the need for a critical analysis of the effects of securitisation and weaponisation approaches towards refugees, and the need for a reconceptualisation of the refugees not as products of push and pull mechanisms, but as human beings seeking better lives.